Answer:
-15x + 39 = -3(5x - 13)
Step-by-step explanation:
a. -3(5x - 13) = -15x + 39
b. -3(5x + 13) = -15x - 39
c. 3(5x - 13) = 15x - 39
d. 3(5x + 13) = 15x + 39
11 3/8 would be the simplified version and 91/8 would be the other way.
Answer:
The answer is around 50,000,000,000 years so its E
Step-by-step explanation:
<span>7x - 2(x + 1) = 6x + 14
</span><span>7x - 2x - 2 = 6x + 14
5x - 2 = 6x + 14
6x - 5x = -2 - 14
x = -16
answer
</span><span>C) -16</span>
Answer:
It is C
Step-by-step explanation:
because 30/200 simplifies to 3/20 and you multiply that times 17000
and get 2550